Soroprevalência da pitiose equina no Rio Grande do Sul, diagnóstico e controle da pitiose em modelo experimental - Weiblen, Carla (2015)
Pythiosis is a granulomatous disease of humans and animals caused by an aquatic oomycete named Pythium insidiosum. In Brazil, equine species is the most affected and the highest occurrence of pythiosis is observed in Brazilian Pantanal. Nowadays, in Rio Grande do Sul (RS), in South of Brazil, there has seen an increase in the number of equine pythiosis. Nevertheless, there is no information about seroprevalence in Brazil. Early diagnosis is the key to success in controlling this infection. Currently, immunotherapy with proteic antigens has been studied as a promising alternative of treatment. The intradermal (ID) route to apply proteic antigen is an option to be evaluated, for both early diagnosis and pythiosis treatment, by using proteic antigens of P. insidioum. In this study it was investigated the seroprevalence of equine pythiosis in the RS State and also it was evaluated and compared the use of proteic antigens of P. insidiosum by the ID route in the diagnosis and control of pythiosis in an experimental model (Oryctolagus cuniculus). To determine the prevalence of equine pythiosis in RS it was used 1002 equine serum samples evaluated by indirect ELISA test. Of the total samples tested, 11.1% (111/1002) were seropositive for equine pythiosis. For the diagnosis it was applied 0.1mL (1.7mg) of proteic antigen by ID route in rabbits (O.cuniculus) (n = 15) divided into three groups: negative control (n = 5), with experimental pythiosis (n = 5) and animals previously immunized with the proteic antigen (n = 5). In order to verify and compare the use of proteic antigen of P. insidiosum by ID as an option of treatment it was used ten rabbits with pythiosis. Five rabbits with pythiosis were treated with 0.1mL proteic antigen applied through ID and other five rabbits by subcutaneous (SC) route with 2mL (34mg) (n = 5). The ID test was able to detect cutaneous reactions in 24h and 72h in all animals exposed to P. insidiosum, as well as it demonstrated sensitivity and specificity comparable with the pattern of diagnosis of pythiosis (indirect ELISA). The treatment proteic antigen of P. insidiosum, by ID and SC route, did not observed difference (P> 0.05) in the size of the lesions. However, the clinical cure affect as 40% of rabbits in both groups. Thus, protein antigen of P. insidiosum by ID may be used in therapeutic protocols of pythiosis in rabbits, also this route as a protocol of pythiosis has other advantages such as lower protein concentration and volume of antigen to control pythiosis. However, research is needed for evaluation of ID route for diagnosis and control of pythiosis in naturally affected species.